2022
DOI: 10.3390/ijms23031844
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Interventions to Mitigate Mitochondrial Dysfunction and Oxidative Stress–Induced Damage in Patients with Bipolar Disorder

Abstract: Bipolar disorder (BD) is characterized by mood changes, including recurrent manic, hypomanic, and depressive episodes, which may involve mixed symptoms. Despite the progress in neurobiological research, the pathophysiology of BD has not been extensively described to date. Progress in the understanding of the neurobiology driving BD could help facilitate the discovery of therapeutic targets and biomarkers for its early detection. Oxidative stress (OS), which damages biomolecules and causes mitochondrial and dop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 393 publications
(484 reference statements)
1
15
0
Order By: Relevance
“…Patients with BD have been found to have altered levels of PUFAs [130][131][132]; an analysis of six studies involving a total of 118 patients with BD-I and 147 healthy controls found erythrocyte DHA and EPA levels to be decreased in patients with BD-I [131]. Supplementation with omega-3 PUFAs has been proposed to be bene icial for many diseases including dementia, cancer, hypertension, diabetes, arthritis, arteriosclerosis and autoimmune disease and evidence supporting the use of ω3 PUFAs in managing BD is particularly promising [133].…”
Section: Bipolar Disorder and Nutrientsmentioning
confidence: 99%
“…Patients with BD have been found to have altered levels of PUFAs [130][131][132]; an analysis of six studies involving a total of 118 patients with BD-I and 147 healthy controls found erythrocyte DHA and EPA levels to be decreased in patients with BD-I [131]. Supplementation with omega-3 PUFAs has been proposed to be bene icial for many diseases including dementia, cancer, hypertension, diabetes, arthritis, arteriosclerosis and autoimmune disease and evidence supporting the use of ω3 PUFAs in managing BD is particularly promising [133].…”
Section: Bipolar Disorder and Nutrientsmentioning
confidence: 99%
“…New treatments for BD are being studied, and most target disparate effector systems, mainly related to molecular targets in neuroplasticity, neurotrophic factors, inflammation, stress, mitochondrial function, and related metabolic pathways [46][47][48]. Clinical trials have demonstrated the efficacy of adjunctive inflammatory modulation with celecoxib in treatment-resistant bipolar depression, showing that add-on celecoxib reduces treatment resistance and enhances antidepressant response in patients with treatment-resistant bipolar depression [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a randomized controlled trial found that a dietary supplement containing omega-3 fatty acids, vitamins, and minerals improved symptoms and quality of life in patients with BD, possibly by correcting nutrient deficiencies and reducing oxidative stress [ 192 ]. Furthermore, a review of the literature suggests that a Mediterranean-style diet, which is high in fruits, vegetables, whole grains, legumes, nuts, and olive oil, may be associated with a lower risk of BD and improve mood in patients with BD, possibly due to its anti-inflammatory and antioxidant properties [ 193 ].…”
Section: Anti-inflammatory Diet and Its Role In Mental Healthmentioning
confidence: 99%